2022
DOI: 10.3389/fceng.2021.803513
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Production of Algal Biofuels by Techno-Economic Optimization of Co-Product Suites

Abstract: Recent techno-economic analysis (TEA) has underscored that for algal biofuels to be cost competitive with petroleum fuels, co-products are necessary to offset the cost of fuel production. The co-product suite must scale with fuel production while also maximizing value from the non-fuel precursor components. The co-product suite also depends on algal biomass composition, which is highly dynamic and depends on environmental conditions during cultivation. Intentional shifts in composition during cultivation are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…As discussed in other recent work [2,24], we reiterate that the future projection scenarios shown in Figure 5 are by no means the only possible combinations of coproducts that support achieving less than $2.5/GGE algal fuel goals, but are initial examples that demonstrate proof of concept based on recent activities to select these products for further TEA consideration. It also should be noted that CAP R&D is simultaneously investigating other alternate processing routes, including additional pretreatment approaches [22], fermentation of high-protein and high-carbohydrate hydrolysates to other fuel and coproduct precursors [6,25], and alternative valorization approaches for the residual solids [26,27]. While the analysis of these options is less exhaustive than that of PU, they may still serve as alternate routes to achieving MFSP targets, especially for more challenging, high-protein feedstocks, which we intend to begin incorporating into future TEA focus.…”
Section: Tea Resultsmentioning
confidence: 99%
“…As discussed in other recent work [2,24], we reiterate that the future projection scenarios shown in Figure 5 are by no means the only possible combinations of coproducts that support achieving less than $2.5/GGE algal fuel goals, but are initial examples that demonstrate proof of concept based on recent activities to select these products for further TEA consideration. It also should be noted that CAP R&D is simultaneously investigating other alternate processing routes, including additional pretreatment approaches [22], fermentation of high-protein and high-carbohydrate hydrolysates to other fuel and coproduct precursors [6,25], and alternative valorization approaches for the residual solids [26,27]. While the analysis of these options is less exhaustive than that of PU, they may still serve as alternate routes to achieving MFSP targets, especially for more challenging, high-protein feedstocks, which we intend to begin incorporating into future TEA focus.…”
Section: Tea Resultsmentioning
confidence: 99%
“…One leading concept for algal biorefining is the parallel or combined algal processing (PAP or CAP) pathway, which fractionates algal biomass into an organic lipid phase, a fermentable aqueous hydrolysate, and a residual solid phase and then upgrades each phase using technology tailored to the chemistry of each fraction. ,, A key aspect of the CAP approach is a pretreatment step, which lyses cells to render the lipids extractable while solubilizing carbohydrates and/or proteins into the fermentable hydrolysate. Historically, CAP has employed a dilute Brønsted acid pretreatment, which proved generally robust for high-carbohydrate and high-lipid algae.…”
Section: Introductionmentioning
confidence: 99%
“…Algal biomass is a promising resource for producing renewable fuels and chemicals, but despite decades of research, algal biorefining for biofuel production remains in a pre-commercial state. While the cost of producing algal biomass is one primary hurdle to commercialization, the technology to convert the biomass to desired products is also in need of development. In particular, recent economic analyses have indicated that high-value co-products are necessary to offset the cost of fuel production if the fuel is to be sold at a price competitive with petroleum-derived fuels, and while many potentially suitable co-products have been identified, , fewer have been demonstrated or validated. The slate of co-products available in a biorefinery also depends strongly upon the fuel production pathway of choice and upstream operations, especially pretreatment of algae biomass to make fuel and co-product precursors available for separation and conversion …”
Section: Introductionmentioning
confidence: 99%
“…Extracted algal residues are produced in fractionation-based approaches to algal conversion, such as the combined algal processing (CAP) pathway. 12 , 13 CAP uses a dilute acid pretreatment and solvent extraction to fractionate wet algal biomass into three distinct intermediate phases: an organic solvent containing extracted lipids, an aqueous hydrolysate enriched with soluble carbohydrates and proteins, and a residual solid phase comprised of the extracted algal residues. 14 Processes to convert extracted lipids into renewable hydrocarbon fuels and non-isocyanate polyurethanes and ferment aqueous hydrolysates into other bioproducts are established, but the valorization of residual extracted solids remains underdeveloped.…”
Section: Introductionmentioning
confidence: 99%